Economic Interdependence between Norway and The European Union Compared to Switzerland and The European Union - Reskiyah, Emy Sri (Universitas Komputer Indonesia, 2023)
Norway and Switzerland have a history of being part of the European Union (EU) and eventually opting out. Though, as a part of the European Economic Area allows Norway to integrate and participate with the EU’s single market. Similarly, Switzerland can participate in and access the European single market through a set of bilateral agreements with the EU. Consequently, both countries must accept a set of rules by the EU. This paper aims to compare and examine the bilateral relations maintained between Norway and the EU compared to Switzerland and the EU in the field of economic cooperation namely the trade and investment sectors in the aftermath of the financial crisis. This paper incorporates two types of analysis. The first part uses quantitative methods of descriptive statistical analysis and is followed by strength, weakness, opportunities, and threat (SWOT) analysis. This paper demonstrates that the bilateral relations between Norway and the EU as well as for Switzerland and the EU have created conditions of interdependence for both the EU and its partners, namely, Norway and Switzerland. Keywords— European Union, Interdependence, Norway, Switzerland